1980
DOI: 10.1111/j.1570-7458.1980.tb02956.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF TEMPERATURE ON THE PRODUCTION OF SEXUALS BY APHIS RUBICOLA UNDER SHORT‐DAY CONDITIONS

Abstract: Higher temperatures led to a less rapid transition from virginopara production to ovipara and male production by apterous, virginoparous Aphis rubicola Oestlund exposed from birth to short‐day conditions. At 19.4° more than 95% of the progeny were sexuals, whereas only ca. 58% were such at 25.1°. A 2‐day cessation of reproduction preceded male production at 19.4° but not at 21.5° and 25.1°. Temperature increases led to the earlier deposition of most progeny, an earlier, more extended period of male production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…The influence of temperature has also been studied extensively in various species, e.g. Aphis rubicola (Oestlund) (Brodel & Schaefers, 1980) and A. fabae (Tsitsipis & Mittler, 1977a, b). These authors found that temperature differentially affected the production of males and that of mating females.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of temperature has also been studied extensively in various species, e.g. Aphis rubicola (Oestlund) (Brodel & Schaefers, 1980) and A. fabae (Tsitsipis & Mittler, 1977a, b). These authors found that temperature differentially affected the production of males and that of mating females.…”
Section: Introductionmentioning
confidence: 99%
“…Στο M. persicae, ένα τυπικό ετερόοικο είδος, η παραγωγή σεξουαλικών μορφών σχετίζεται με τη διάρκεια της σκοτόφασης. Πιο συγκεκριμένα, αυτή εξαρτάται από τον αριθμό και τη διάρκεια των σκοτοφάσεων που προάγουν την παραγωγή τους (Blackman 1975b (Brodel & Schaefers 1980).…”
Section: θρέψηunclassified